2009
DOI: 10.2165/11318960-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Messages about Black-Box Warnings

Abstract: FDA and US lay media reports about medication black-box warnings presented different information. This may reflect a difference in underlying motivation for reporting of news about risks of adverse drug events. It may also indicate a lack of agreement and understanding about the best methods to communicate risk information to the public, thus indicating areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…23 Furthermore, the publicity itself may affect the response to FDA label changes and warnings. 24,25 We previously found that the widely publicized FDA warnings for antidepressants and suicidality led to substantial reductions in antidepressant use and simultaneous increases in suicide attempts by poisonings among youth, 12 suggesting that excessive caution might have resulted in reduced use of effective therapies for patients who could benefit from them.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, the publicity itself may affect the response to FDA label changes and warnings. 24,25 We previously found that the widely publicized FDA warnings for antidepressants and suicidality led to substantial reductions in antidepressant use and simultaneous increases in suicide attempts by poisonings among youth, 12 suggesting that excessive caution might have resulted in reduced use of effective therapies for patients who could benefit from them.…”
Section: Discussionmentioning
confidence: 99%